A alfabetização inclusiva com enfoque no espectro autista: uma revisão narrativa - Neves, Caroline Salvador (Universidade Federal de São Carlos, 2025)
Literacy for children with Autism Spectrum Disorder (ASD) is a right guaranteed by national and international legislation, such as the 1988 Federal Constitution, the Brazilian Inclusion Law (Law nº 13.146/2015), and the Convention on the Rights of Persons with Disabilities (UN, 2006; BRAZIL, 2015). In the context of inclusive education, this right requires pedagogical practices grounded in the uniqueness of the autistic learner, respecting their pace and ways of learning. This study aims to discuss, through a narrative review of the scientific literature, the literacy process of children with ASD, considering the difficulties encountered in inclusive school settings. To achieve this, the paper is organized into three sections: first, a brief contextualization of Special Education in Brazil is presented; next, some international milestones of Inclusive Education and relevant policies in Brazil are outlined; finally, the literacy process of children with ASD is examined, addressing pedagogical practices and the challenges faced in regular schools regarding inclusion and the development of these students. Based on the literature consulted, the literacy process of children with ASD highlights the need for specific teacher training; the importance of collaborative work among teachers and other education professionals; as well as the use of adapted technologies and materials, and the value of playful, visual, and affective practices as resources for literacy. It is also emphasized that, although progress has been made in terms of public policies and academic production, gaps persist in teachers’ continuing education, in the structuring of effective classroom practices, and in the meaningful inclusion of students with ASD in the literacy process. Thus, the urgency of a pedagogical approach centered on diversity, respect for differences, and the guarantee of the right to quality education for all is reinforced.
Inclusive literacy with a focus on the autism spectrum: a narrative review
Keywords: Alfabetização; Transtorno do Espectro Autista; Educação inclusiva; Práticas pedagógicas; Literacy; Autism Spectrum Disorder; Inclusive education; Pedagogical practices; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade